IL37 dampens the IL1β-induced catabolic status of human OA chondrocytes. (7th December 2016) - van Geffen, Ellen W.; van Caam, Arjan P. M.; van Beuningen, Henk M.; Vitters, Elly L.; Schreurs, Wim; van de Loo, Fons A.; van Lent, Peter L. E. M.; Koenders, Marije I.; Blaney Davidson, Esmeralda N.; van der Kraan, Peter M.
Abstract : Objective. A crucial feature of OA is cartilage degradation. This process is mediated by pro-inflammatory cytokines, among other factors, via induction of matrix-degrading enzymes. Interleukin 37 (IL37) is an anti-inflammatory cytokine and is efficient in blocking the production of pro-inflammatory cytokines during innate immune responses. We hypothesize that IL37 is therapeutic in treating the inflammatory cytokine cascade in human OA chondrocytes and can act as a counter-regulatory cytokine to reduce cartilage degradation in OA. Methods. Human OA cartilage was obtained from patients undergoing total knee or hip arthroplasty. Immunohistochemistry was applied to study IL37 protein expression in cartilage biopsies from OA patients. Induction of IL37 expression by IL1β, OA synovium-conditioned medium and TNFα was investigated in human OA chondrocytes. Adenoviral overexpression of IL37 followed by IL1β stimulation was performed to investigate the anti-inflammatory potential of IL37. Results. IL37 expression was detected in cartilage biopsies of OA patients and induced by IL1β. After IL1β stimulation, increased IL1β, IL6 and IL8 expression was observed in OA chondrocytes. Elevated IL37 levels diminished the IL1β-induced IL1β, IL6 and IL8 gene levels and IL1β and IL8 protein levels. In addition to the reduction in pro-inflammatory cytokine expression, IL37 reduced MMP1, MMP3, MMP13 and disintegrin and metalloproteinase with thrombospondin motifs 5 gene levels and MMP3 and MMP13 protein levels. Conclusion. IL37 is induced by IL1β, and IL37 itself reduced IL1β, IL6 and IL8 production, indicating that IL37 is able to induce a counter-regulatory anti-inflammatory feedback loop in chondrocytes. In addition, IL37 dampens catabolic enzyme expression. This supports IL37 as a potential therapeutic target in OA.